Analyzing the Effect of Local Government Competition on Green Total Factor Productivity From the Market Segmentation Perspective in China—Evidence From a Three-Stage DEA Model - Tang, Juan; Qin, Fangming (Frontiers in Environmental Science, 2021)
Under the dual background of the Chinese-style fiscal decentralization system (vertical competition) and promotion tournament system (horizontal competition), the economic development system dominated by the government determines that local government competition is a crucial factor affecting green total factor productivity (GTFP). Moreover, market segmentation, as one of the important strategic tools for local government competition, will have a significant impact on GTFP due to the implied changes in production efficiency and blocked factor flows. This paper applies the GMM method and the mediation effect model to explore the relationship between local government competition and GTFP from the perspective of market segmentation using statistical data from 30 provinces from 2006 to 2017 in China. The results show that, on the whole, local government competition significantly inhibits the promotion of GTFP. Local government competition also has a negative impact on GTFP by promoting market segmentation. The coefficient of market segmentation as a mediation variable is statistically significant. In terms of regional heterogeneity, in the eastern region, there is not evidence that local government competition has a significant inhibitory effect on GTFP, and the intermediary effect of market segmentation has not been found. In the central and western regions, GTFP is still significantly inhibited by local government competition, and the mediation effect of market segmentation is significant. After the robustness test is performed, the above empirical results are still robust.